Strategies to be used to develop the intercultural communicative competences (2016)
Modern languages students need develop the intercultural communicative competence in order to have good command in the idioms learned, the research proposes strategies to improve communication skills. This article presents in theoretical framework main concepts with the purpose of understanding the meaning of Intercultural communicative competence, in addition it includes some notions about ICT‟s in the developing of competences and it emphasizes the role of the teacher and students as active participants in the process towards the development of ICC. This document cited authors as Byram, M., Katan, D. Gudykunst, W., Fantini, A., Kutukdjian, G., Corbett, J. and other, who through their different points of view provide and clarify the different concepts mentioned in this Lit Review, without forget some useful standards for Colombian education and development Intercultural Communicative Competences. Conclusions suggest to insert programs focus on Intercultural competence in curriculums of modern languages, these should include technology tools and intercultural meetings with other people culturally different.